The effect of an export levy on the Malaysian cocoa industry - Shamsudin, Mad Nasir (Universiti Putra Malaysia Press, 1998)
This study attempts to elucidate the economic implications of an export levy on the Malaysian cocoa industry. The results indicate that the imposition of an export levy would lower producer prices and raise export prices. Hence production and exports would decline. Domestic utilization and imports, on the other hand, would increase.